Designing an Optimization of Orientation System toward Moving Object in 3-Dimensional Space Using Genetic Algorithm - Feishal Reza; Panca Mudjirahardjo; Erni Yudaningtyas (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
This research offers a scheme of orientation system toward moving object in 3-dimensional space that using Stereo Vision Camera. The system benefits in giving an alternative solution in projecting practically without manual identification by conventional measuring device. The result of the projection in the system is in the form of coordinate position information (x, y, z), the length, the width, and the height of the object detected. The output displayed in the real-time digital image with 3-dimensional modeling. In the process of the object identification, there was a stage when an image was converted from colored image to binary image. But the conversion used the threshold method which was considered less efficient when an object moved. As consequence, the new adaptive method in solving the problem was needed. Genetic Algorithm was proposed as the optimization method because it was considered suitable with the emerging problems. In the optimization process, genetic algorithm was in a task of searching process and determining the threshold value as the process of creating binary image. The result shows an increased accuracy in the identification process after the system had been optimized by the Genetic Algorithm (GA).